2017 European Conference on Mobile Robots (ECMR) 2017
DOI: 10.1109/ecmr.2017.8098665
|View full text |Cite
|
Sign up to set email alerts
|

Deep Detection of People and their Mobility Aids for a Hospital Robot

Abstract: Robots operating in populated environments encounter many different types of people, some of whom might have an advanced need for cautious interaction, because of physical impairments or their advanced age. Robots therefore need to recognize such advanced demands to provide appropriate assistance, guidance or other forms of support. In this paper, we propose a depth-based perception pipeline that estimates the position and velocity of people in the environment and categorizes them according to the mobility aid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 18 publications
(27 reference statements)
1
9
0
Order By: Relevance
“…Both Adam and AdamS led to poor performance on both datasets, creating many low-accuracy detections during the test phase. On the other hand, AdamW achieved good results, obtaining comparable results with Vasquez et al [47,63] on the MobilityAids dataset and acceptable results on the MOT17Det dataset. More about these results can be found in Section 5.…”
Section: Gradient Descent Optimizer and Learning Rate Schedulersupporting
confidence: 51%
See 1 more Smart Citation
“…Both Adam and AdamS led to poor performance on both datasets, creating many low-accuracy detections during the test phase. On the other hand, AdamW achieved good results, obtaining comparable results with Vasquez et al [47,63] on the MobilityAids dataset and acceptable results on the MOT17Det dataset. More about these results can be found in Section 5.…”
Section: Gradient Descent Optimizer and Learning Rate Schedulersupporting
confidence: 51%
“…The first considered dataset is Mobility Aids, which was created and used by Vasquez et al [47]. It contains roughly 17,000 RGB, Depth, and DepthJet images grouped into sequences.…”
Section: Existing Datasetsmentioning
confidence: 99%
“…There have been previous studies of teleoperated mobile robots to assist with tasks in hospitals. However, most of those robots traveled on a predetermined path and performed a predetermined action [20]- [28], so they did not require much teleoperation. In addition, there have been reports of robots in the medical field that can be operated wirelessly, such as through the Internet [31], and Dallal et al [32] showed that a hospital mobile robot could be controlled over a wireless local area network.…”
Section: Related Workmentioning
confidence: 99%
“…One mathematical framework of generative models is the Hidden Markov Model (HMM) which is able to respect the time-domain and noisy sensor data of a process. Applications to robotics and grid maps have shown the incorporation of learning and decoding of hidden property information from the environment which makes HMMs a suitable approach to infer properties out of the semantical grid maps (Stachniss, 2009 ; Walter et al, 2013 ; Vasquez et al, 2017 ).…”
Section: Related Workmentioning
confidence: 99%